A trip too far : ecotourism, politics, and exploitation - Duffy, Rosaleen (Earthscan, 2002)
"Tourism is the world's largest industry, and environmentally sustainable tourism, or 'ecotourism', has become a major area of interest for governments, the private sector and international lending institutions. It is regarded as a way of allowing economic development whilst protecting against environmental degradation, especially in those countries with fragile ecosystems." "Does ecotourism deliver real environmental benefits or is it just a marketing opportunity - 'green greed'? Through extensive use of case study and interview material, A Trip Too Far presents the first critical analysis of the impacts of ecotourism, both positive and negative, and shows how, given the right political context and regulation, it can work to support conservation and local economies." "The ideas and proposals that are presented will be important for the development of ecotourism around the globe and will be vital reading for academics in development and environmental studies and those working in environmental non-governmental organizations and the tourism industry."--Jacket.